The Future of the Law of the Sea: Bridging Gaps Between National, Individual and Common Interests (2017)
The present book is the final product of the work of Marsafenet, which is a network of experts on maritime safety and security, sponsored by the COST funding scheme under H2020. Marsafenet is a collaborative partnership that works together in addressing recent law of the sea issues. The work of Marsafenet has led to a number of symposia held in various countries, the publication of several books and the creation of the MarSafeLaw Journal, an open access, peer-reviewed journal. It must be envisaged that this remarkable collective effort will not vanish with the end of Marsafenet—the network of friendships and scholarly collaboration must continue, as must the MarSafeLaw Journal.